Eksistensi Kampung Dalam Perspektif Ekologis : (Studi Kasus Di Kampung Tering Lama Kabupaten Kutai Barat) - Christensen Eldisa Joshua; Budiman Budiman; Badruddin Nasir; Rita Kalalinggi; E. Letizia Dyastari (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2022)
The land of a river bank village of Tering Lama continues to erode, and it could cause this village to disappear. This research attempts to study the factors that influence its existence in order to survive. This study uses a qualitative descriptive research method to determine such factors. The study found that there are some influentual factors, namely traditions, habits, social interaction, environmental conditions, and the role of the government. The most determining ones are the environmental conditions and the role of the government. In fact, while some have left the river bank area, a considerable number of people of Tering Lama village can still survive from degraded environmental conditions such as landslides because they are very enthusiastic in protecting the environment to preserve their traditional culture that has existed for so long. In cooperation with village government, their important effort was placing sand bags in the eroded river bank as sheet pile. Recently, they had been supported by the district government by constructing gabion wire as sheet pile. All of these ecological efforts are of importance in preserving their culture and tradition.